Studi Empiris Kurva Phillips New Keynesian di Indonesia - Sukarsih Sukarsih; Diah Setyorini Gunawan; Ratna Setyawati Gunawan (Ilmu Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Unsoed, 2011)
ABSTRACT The present research was aimed to analyze New Keynesian Phillips Curve (NKPC) in Indonesia using time series data for 39 years, start from 1970 until 2008. We use generalized method of moments (GMM) for estimation and hypothesis testing for the following reason: GMM estimators can be constructed without specifying the full data generating process (which would be required to write down the maximum likelihood estimator). Price rate and unemployment rate were used as variables that will be estimated in this research.The result shows that all variables in NKPC estimation are significant. Inflation rate and unemployment rate have positive correlation. Our results tend to support the NKPC. Empirical evidence seemed to subsequently back up Friedman’s argument, as the 1970s saw the “stagflation” combination of high inflation and high unemployment that the Phillips curve relationship seemed to rule out. Keywords: New Keynesian Phillips Curve, generalized method of moments